Strategies for Enhancing Females Participation in Technical, Vocational Education and Training (TVET) in Nigeria - Oluniyi, Adelakun; Itohan, Oviawe Jane; Garba, Barfa (Advances in Social Sciences Research Journal, 2015)
There is generally low enrolment of female students in Technical, Vocational Education and Training (TVET) in Nigeria. This study was carried out to determine strategies to enhance female participation in TVET in Nigeria hitherto dominated by males. The study adopted a survey research design. Three research questions were formulated to guide the study. The population of 153 comprised 95 female technical teachers, 58 female administrators in the technical colleges and skill acquisition centres in the zones covered by the study. The instrument was face-validated by three TVET experts in University of Nigeria, Nsukka. Cronbach Alpha was used to establish the reliability and a reliability coefficient of 0.85 was obtained. Mean and standard deviation were used to analyse the data collected. The strategies determined were agreed upon as enhancement strategies as well as benefits accruable if females embrace TVET. It was recommended that wives of State governors should establish women organization in technology to sensitize females on the benefits of TVET. Money should be earmarked by government and other stake holders in technical education to ensure effective running of female-enhanced TVET programme. KEYWORDS: Technical, Vocational Education and Training, Females in TVET, Participation, Strategies.